Replication origins and a sequence involved in coordinate induction of the immediate-early gene family are conserved in an intergenic region of herpes simplex virus. - Whitton, J L (1984)
We have determined the structure of the 5' portion of herpes simplex virus type 2 (HSF-2) immediate-early (IE) mRNA-3 and have obtained the DNA sequence specifying the N terminus of its encoded polypeptide, Vmw182, its untranslated leader and the intergenic region between IEmRNAs-3 & 4/5. Comparison of the HSV-2 intergenic sequences with the HSV-1 equivalent region identifies several conserved regions: (1) an AT-rich element with core consensus TAATGARAT which is likely to be the 'activator' sequence through which coordinate induction of the IE gene family is mediated. (2) GC-rich and GA-rich tracts, found in a wide variety of eukaryotic promoters, which vary in position and orientation between HSV-2 and HSV-1 and which represent modulators of transcription. (3) TATA homologies present 15-25 base pairs (bp) upstream of mRNA 5' termini. (4) a 137bp direct repeat in HSV-2 which contains sequence almost identical to the HSV-1 replication origin.